Bedside assessment of swallowing in elderly subjects using psychotropic drugs - Fioravanti,Marisa Portes (2011)
Neuroleptic drugs are used in several mental disorders, but are suspected of causing oropharyngeal dysphagia, mainly in the elderly. AIM: To study the effect of neuroleptic agents on swallowing of institutionalized older people. MATERIAL AND METHOD: A cross sectional study of swallowing in 47 subjects that either used or did not use neuroleptic drugs. Bedside swallowing tests with foods of four different consistencies were carried out. RESULTS: There was no significant difference between the two groups. Users of neuroleptic medications showed a higher percentage of multiple swallowing while non-users had a higher percentage of oral food escape. CONCLUSIONS: Neuroleptic agents alone do not affect the mechanism of swallowing in the elderly; nonetheless. Further studies with a larger number of individuals and specific swallowing tests are needed